Sustainability and Energy Performance in the Real Estate Market. - Andrea Ciaramella (Environmental Science and Sustainable Development, 2016)
One of the main economic benefits associated with the sustainable character of buildings is certainly the reduced use and energy consumption. The savings can be very significant, especially when you consider that a non-residential building, energy-efficient point of view, can be achieved a power savings of 30% (Kats, 2003). This, combined with the rising energy prices and growing awareness of environmental issues, has gradually shifted the demand towards buildings with good sustainable features; as a result, the concept of "sustainability" has become a real "driver" for designers " (Turner and Frankel, 2008).